Explore the world of broadcasting with Astro Awani - Siti Sarah, Mohamad Rajimi (2018)
Kuala Lumpur, 27 Februari – A total of 30 members from Mass Media Club, Universiti Malaysia Pahang (UMP) organized an educational visit to Astro Awani Studio with the objective to get an exposure and experience in broadcasting and journalism.